LYMPHOCYTE APOPTOSIS AND ADVERSE PREGNANCY OUTCOME (Iraqi Journal of Medical Sciences, 2004)
Background: Apoptotic cell death plays an important role in cell biology and pathology including studies of embryonic development, pathogenesis of diseases, and the response of cell to therapy. Aim of the study: To clarify the relation between apoptosis and oxidative stress in different pregnancy outcome, namely miscarriage and PET. Patient and methods: The study involved 30 pregnant women; 10 were preeclampsia, 10 had miscarriage (before 20 weeks gestation).Surface morphological changes of lymphocyte apoptosis were diagnosed by phase contrast and Interference contrast microscopy. Lipid peroxidation using thiobarbituric acid reactive species (malondialdehyde). Erythrocyte glutathione was estimated by Lang et al method, Zinc and Copper were estimated using atomic absorption spectrophotometer. Statistical analysis done using unpaired student T- test, and correlation coefficient.Results: We found a significant increase in lymphocyte apoptosis in preeclamptic patients (p